ECG Repolarization Waves: Their Genesis and Clinical Implications - Hlaing, Thinn (Ann Noninvasive Electrocardiol, 2005)
The electrocardiographic (ECG) manifestation of ventricular repolarization includes J (Osborn), T, and U waves. On the basis of biophysical principles of ECG recording, any wave on the body surface ECG represents a coincident voltage gradient generated by cellular electrical activity within the heart. The J wave is a deflection with a dome that appears on the ECG after the QRS complex. A transmural voltage gradient during initial ventricular repolarization, which results from the presence of a prominent action potential notch mediated by the transient outward potassium current (I(to)) in epicardium but not endocardium, is responsible for the registration of the J wave on the ECG. Clinical entities that are associated with J waves (the J‐wave syndrome) include the early repolarization syndrome, the Brugada syndrome and idiopathic ventricular fibrillation related to a prominent J wave in the inferior leads. The T wave marks the final phase of ventricular repolarization and is a symbol of transmural dispersion of repolarization (TDR) in the ventricles. An excessively prolonged QT interval with enhanced TDR predisposes people to develop torsade de pointes. The malignant “R‐on‐T” phenomenon, i.e., an extrasystole that originates on the preceding T wave, is due to transmural propagation of phase 2 reentry or phase 2 early afterdepolarization. A pathological “U” wave as seen with hypokalemia is the consequence of electrical interaction among ventricular myocardial layers at action potential phase 3 of which repolarization slows. A physiological U wave is thought to be due to delayed repolarization of the Purkinje system.